Brominated Luciferins Are Versatile Bioluminescent Probes. (8th December 2016) - Steinhardt, Rachel C.; Rathbun, Colin M.; Krull, Brandon T.; Yu, Jason M.; Yang, Yuhang; Nguyen, Brian D.; Kwon, Jake; McCutcheon, David C.; Jones, Krysten A.; Furche, Filipp; Prescher, Jennifer A.
Abstract: We report a set of brominated luciferins for bioluminescence imaging. These regioisomeric scaffolds were accessed by using a common synthetic route. All analogues produced light with firefly luciferase, although varying levels of emission were observed. Differences in photon output were analyzed by computation and photophysical measurements. The brightest brominated luciferin was further evaluated in cell and animal models. At low doses, the analogue outperformed the native substrate in cells. The remaining luciferins, although weak emitters with firefly luciferase, were inherently capable of light production and thus potential substrates for orthogonal mutant enzymes. Abstract : Bright ideas ! Multicellular imaging and other applications of bioluminescence technology require diverse luciferin architectures. Here, we report a set of brominated luciferins that are robust light emitters and exhibit unique photophysical properties. These molecules can also be diversified by cross‐coupling reactions to access an assortment of imaging probes.